Progranulin-associated PiB-negative logopenic primary progressive aphasia - Josephs, Keith A. (2014)
The logopenic variant of primary progressive aphasia (lvPPA) strongly associates with Alzheimer’s disease, but can also associate with frontotemporal lobar degeneration. We aimed to assess the frequency of lvPPA in patients with speech and language disorders without β-amyloid deposition, and to perform detailed neuroimaging and genetic testing in such lvPPA patients. Seventy-six patients with a neurodegenerative speech and language disorder and Pittsburgh compound B (PiB) PET imaging demonstrating no β-amyloid deposition were analyzed. Six lvPPA patients (8 %) were identified. All six underwent progranulin (GRN) gene testing. Structural abnormality index maps and Cortex ID analysis were utilized to assess individual patterns of grey matter atrophy on MRI and hypometabolism on 18-F fluorodeoxyglucose (FDG) PET. Statistical parametric mapping was used to perform MRI and FDG-PET group comparisons between those with (GRN-positive) and without (GRN-negative) progranulin mutations. All six lvPPA patients showed left temporoparietal atrophy and hypometabolism. Three patients (50 %) were GRN-positive. Speech, language, and neurological and neuropsychological profiles did not differ between GRN-positive and negative patients, although GRN-positive patients had family histories, were on average 8 years younger, and had lower PiB-PET ratios. All six patients showed similar patterns of atrophy and hypometabolism, although, as a group, GRN-positive patients had more severe abnormalities, particularly in anteromedial temporal lobes. Logopenic PPA accounts for a small minority of neurodegenerative speech and language disorders not associated with β-amyloid deposition. Identification of such patients, however, should prompt testing for GRN mutations, since GRN-positive patients do not have distinctive features, yet account for 50 % of this patient population.